Process audit in a beverage industry - line efficiency and downtime analysis, a case study. (24th September 2021) - Macarthur, John; Narayan, Sumesh; Ananthanarayanan, Rajeshkannan; Seenivasagam, Devi Rengamani; Swami, Kamendra Narayan
Continuous improvement is the sustaining force for a company to ever stand in the market in every perspective. Particularly in the production process, a steady, quick and flexible flow has to be maintained. Although, the case industry has a vast market in Fiji to cater for the beverage need that indicates the product design is doing well, the process flow finding it challenging to cope up with meeting the demand continuously. Therefore, a process audit was conducted, and the data has been observed to carry out line efficiency and downtime analysis. The former analysis is carried out using upper bound approach; thereby possible optimised buffer stocks have been found out. Whereas the latter analysis is performed using some quality control tools at the bottleneck station, which helped to identify a significant few rather than many trivial issues that disrupt the process flow. Finally, the solutions are devised using brainstorming exercise.